Iberian-indigenous malice and institutionalization deficit: the origins of a lazy work mentality in Colombia. - Cabrales Salazar, Omar; Martínez Herrera, Rafael (Crime, Law & Social Change, 2020)
This article is the result of the historical and documentary review of an investigation which, from a qualitative approach, intended to find the base that built the identity of Colombian people and their behavior towards work and the institutions. It discusses the consequences of the XV Century Spanish conquest model, the deficit of institutionalization and the initial concept of work in the creation of institutions as an essential condition for social cohesion. All of which might still affect the understanding of illegality as a favorable environment for the emergence of multiple informal or marginal trades in some social spheres. These contexts end up consolidating themselves as the basis of an illegal 'industry' permanently reinventing itself, giving rise to the development of certain skills, including Iberian-indigenous malice, necessary for survival in the Colonial period, that later could have had an impact on the emergence of illegal behavior.